Efektivitas Edukasi Dengan Emotional Demonstration dan Video CIKA Terhadap Pengetahuan dan Sikap Pencegahan Anemia dan KEK Pada Wanita Premarital - Yanik Muyassaroh; Anjar Astuti (ARTERI : Jurnal Ilmu Kesehatan, 2026)
Anemia and chronic energy deficiency (CED) remain relatively prevalent in Indonesia. CED affects 17.3% of pregnant women and 14.5% of non‑pregnant women of reproductive age (15–49 years). Among females aged 15–19 years, the largest proportions are pregnant adolescents (33.5%) and non‑pregnant adolescents (36.3%), with anemia prevalence of 48.9% in pregnant women and 32% in adolescent girls. To secure maternal and infant health and to improve women’s productivity and quality of life, health promotion is essential to prevent anemia and CED among premarital women. An effective way to increase their knowledge is to use engaging approaches and media, such as emotional demonstration modules and animated videos (ATIKA: Ati, Telur, Ikan as iron‑rich foods and “Isi Piringku”). This study aimed to analyze the effectiveness of education using emotional demonstration (ATIKA and Isi Piringku) and the CIKA animated video (preventing and overcoming anemia and CED) on knowledge and attitudes toward prevention of anemia and CED in premarital (unmarried) women. A quasi‑experimental design with a randomized prospective pretest–posttest control format was employed. The first group received the emotional demonstration intervention, while the second group received the video intervention. Results showed that both the emotional demonstration and audiovisual groups exhibited increases in mean knowledge and attitude scores; the change was statistically significant (p = 0.0001 for knowledge and p = 0.0001 for attitudes). Conclusion: the emotional demonstration method was more effective than the audiovisual medium in improving knowledge and attitudes for the prevention of anemia and CED. Implementation of health education using emotional demonstration is recommended to enhance knowledge and attitudes.